GAMBARAN KLINIS DAN LAMA RAWAT INAP PASIEN DIABETES MELLITUS BERDASARKAN STATUS KOMPLIKASI DI RSUD DR. HASRI AINUN HABIBIE - Siti Maryam Latifatul Zannah Ngabito; Tesya Oktavia Mait; Gladis A Ismail; Susanly Ainun Handoko (Pusat Studi Ekonomi, Publikasi Ilmiah dan Pengembangan SDM, 2026)
Complications of diabetes mellitus contribute to the length of hospital stay. This study aims to describe the demographic characteristics, complication status and length of hospital stay of patients with diabetes mellitus based on their complication status at Dr Hasri Ainun Habibie General Hospital, Gorontalo. This was a quantitative descriptive study with a comparative approach, utilising secondary data from inpatient medical records for the period January 2022 to December 2024. The results indicated an upward trend in the number of cases. The majority of patients were female and in the 45–54 age group. The majority experienced complications, with the distribution showing that diabetes mellitus was accompanied by other complications (non-ulcer-related), and the most common length of hospital stay was 4–7 days. In the group with a hospital stay of ?7 days, diabetes mellitus accompanied by ulcers was predominant. Strengthening diabetes management at the primary care level is necessary to prevent complications and reduce the length of hospital stay.